Development of a nanoscale measurement system - Akhanova, N.E.; Darznek, S.A.; Zhelkobaev, J.E.; Gabdullin, M.T.; Yerlanuly, Y.; Batryshev, D.G. (Recent Contributions to Physics, 2018)
The work is devoted to measuring linear displacements in the nanoscale, analyzing the features of this kind of work, ensuring the unity of measurements and stability of the measured physical quantity, the reliability of the results and their linkage to the State Standard. The criteria that must be met by methods and means of precision measurements in the nanoscale, as well as methods and means for acquiring and presenting the information obtained. The analysis of the main sources of errors is made and the results of these studies are presented in [1]. The features of the construction of measuring systems, as well as the problems of calibration of phase measurements in optics, are considered. The problems of an applied nature are considered: the measurement of real displacement of objects in the nanoscale, their speed and acceleration, as well as the introduction of the developed methods into the field of practical application. The results obtained in solving experimental and applied problems using methods and means of numerical heterodyning are presented. The developed "interferometer-phase meter" measuring system allows online investigating of complex piezoceramic structures used in various devices as actuators.
Keywords: laser, linear displacement, nanoscale, interferometry, phase shift angle (PSA)